Meta-Analysis of Hypertension Trials Confirms Benefits of Blood Pressure Lowering - Cunningham, Muriel (MD Conference Express, 2013)
This article presents the results of a meta-analysis of blood pressure (BP)-lowering trials that have been published over the past 47 years. This meta-analysis of hypertension randomized trials was conducted to determine the effect of differential BP lowering on hard clinical outcomes.